Pengaruh Kepribadian dan Etika Kerja Terhadap Kinerja Karyawan di PT Cimb Niaga Cabang Slipi - Eneng Wiliana; Dian Aprilia Surya (MAMEN: Jurnal Manajemen, 2022)
The purpose of this study is to determine the effect of personality and work ethics on employee performance. The research approach in this study is quantytative research. A total of 35 respondents were obtained. Statistical test, asumsi classic test, determination coefficients test, partial hypotesis test (t test) and simultaneous hyphothesis test (F test). The results showed that the personality and work ethics on employee performance, with determination of 73,3% and the remaining 23,3% was influenced by other factors and resulting multiple regression equation was Y = 12,092 + 0,791 X1 + 0,113 X2. The results of the analysis of this study indicate that there is an influence and significant personality on employee performance as evidenced in the value of tcount > ttable (9,438 > 1,692) and there is an influence and sifnificant work ethic on employee performance as evidenced in the value tcount > ttable (7,366 > 1,692). While personality and work ethic simultaneously influence and significantly affect employee performance, this can be seen from the Fcount > Ftable (43,88 > 3,29) with a significant level of 5%.